Reform and the structure of the Indian economy : output-value added symbiosis - Datta, Madhusudan, 1953- (Cambridge : Cambridge University Press, 2020)
This book studies pitfalls in value added accounting of sectoral growth in real terms in the context of liberalisation of the Indian economy. Growth of sectoral gross value added can systematically deviate from that of final expenditure (and gross output), even maintaining the broad national accounting identity between the aggregates. For an investigation along these lines, input-output transactions tables provide invaluable information. The book discusses at length tricky questions of data handling and issues in interpretation of data. As the growth rate of the economy accelerated, economists observed that growth of value added came mostly from the service sector. Can the service sector maintain the momentum if manufacturing fails to get charged up in spite of all reforms aimed at this objective? The book studies this question in depth and addresses an audience interested in studying the Indian economy.
Introduction: the take-off -- Growth and structural change since 1978-79: issues in measurement -- Sectoral shares in Indian GDP: how to regard it? -- Sectoral growth: GVA-output dichotomy -- Manufacturing sector in the Indian economy: paradox of growth and stagnation -- Growth and sectoral GVA adjustments -- Demand for intermediate services -- Linkages and key sectors in the Indian economy -- Conclusion: a perspective of Indian economic growth.
Title from publisher's bibliographic system (viewed on 20 Mar 2020).
Keywords: Service industries -- Economic aspects -- India; India -- Economic conditions -- 1947-